The impact of digital empowerment on open innovation performance of enterprises from the perspective of SOR - Lingling, Liang; Ye, Li (Frontiers in Psychology, 2023)
As China's digital transformation index continues to climb and market openness increases, the active implementation of open innovation embedded in digital innovation eco-networks is key to implementing sustainable innovation-driven strategies. The widespread use of digital technologies has broken through the traditional closed boundaries of enterprises and enhanced technology exchange, information communication and R&D collaboration with other innovation agents. However, many enterprises' digital empowerment efforts only stay at the level of digital technology, but do not rise to the level of corporate strategy. How to comprehensively promote the change of enterprise digital empowerment and help enterprises build a sustainable open innovation ecosystem needs further research. This paper analyzes the transmission mechanism of digital empowerment on open innovation from a cognitivist perspective using structural equation modeling combined with stimulus-organization-response (SOR) theory. The conclusions indicate that: (1) in the era of digital economy, digital empowerment emphasizes the initiative and self-adaptation of companies to find a sustainable digital path for themselves; (2) organizational emotional competence and Chaxu climate. This paper provides an in-depth analysis and discussion, and offers insights for effectively improving corporate innovation performance.